1982
DOI: 10.1111/j.1365-2591.1982.tb01274.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in pulpal inflammation beneath surface‐sealed silicates

Abstract: The authors acknowledge the financial support of Amalgamated Dental International, and the technical help from the staff within he Department of Oral Pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 23 publications
(17 reference statements)
5
20
0
Order By: Relevance
“…Whilst choice of drill speed has been suggested to be a matter of personal preference, this study has shown the consequences of inadequate coolant during cavity cutting and the possible effects of different drill speeds on pulpal activity. Absence of water coolant caused the greatest loss of pulpal cell survival, which concurs with previous views (Tobias et al. 1982) and the resulting injury prevented a reactionary dentinogenic response.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Whilst choice of drill speed has been suggested to be a matter of personal preference, this study has shown the consequences of inadequate coolant during cavity cutting and the possible effects of different drill speeds on pulpal activity. Absence of water coolant caused the greatest loss of pulpal cell survival, which concurs with previous views (Tobias et al. 1982) and the resulting injury prevented a reactionary dentinogenic response.…”
Section: Discussionsupporting
confidence: 91%
“…Other factors that have been claimed to be potential sources of pulp injury during cavity restoration include: conditioning of the dentine cavity wall (Tziafas et al. 1993), method of placement of the restorative material (Kirk & Meyer 1992) and choice of cavity restoration product (Tobias et al. 1982).…”
Section: Introductionmentioning
confidence: 99%
“…[2526] Mild inflammatory processes may at times cause the formation of condensing apical periodontitis, mostly involving the mandibular first molar. [27] Various studies have suggested that the key factor in success of VPT is the sealing ability of the material;[28] on the other hand, the most important cause of failure is bacterial recontamination. [29] The CEM cement favourably prevents microleakage and has sealing ability comparable to MTA and superior to IRM.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Other studies have also suggested that the most important factor in the dental pulp healing process is the sealing ability of the material. [28] NEC prevents microleakage with a sealing ability superior to IRM and comparable to MTA. [22] Therefore, as a pulpotomy material, it can prevent recontamination of dental pulp, which can occur with CH compounds.…”
Section: Discussionmentioning
confidence: 99%